(untitled) (Homoeopathy for All, 2023)
One of the most stubborn remedy in our Materia medica which is constitutionally deep acting, pathogenetic product of disease. It has been used to immunize people who are affected from inherited effect of tuberculosis. It is effective to restore our vital reaction, along with the pathological changes. Intellectual curious individual who tends to grasp the things innovatively and works in effortless manner, to achieve their goal. An independent individual who doesn’t expect anyone to work with them neither get attached to anyone. They are frivolous ones. People of Tuberculinum personality are unpredictable in their mood and fun loving personality with relaxed attitude, seems very attractive. Childhood abuse in the past history of the individual which may reflect in the present scenario in the form of various events. Weight of his past events made him repulsive sometime. Otherwise, he is predominantly an attractive person with desired aim. They are goal- oriented, intelligent, also posses’ adaptability.